2016
DOI: 10.1213/ane.0000000000001140
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Inhibits HCN Currents in Rat Spinal Substantia Gelatinosa Neurons

Abstract: Published ahead of print January 11, 2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Averaged spike frequencies vs. the hyperpolarizing pre-pulses were shown in the right panel ( n = 13 cells in nine rats). Meanwhile, we found that the mean latency to peak of the rebound depolarization was 69.6 ± 19.3 ms at −120 pA. Our previous study has shown that SG neurons exhibit various firing patterns, encompassing tonic firing, delayed firing, single spike, initial burst, phasic firing, gap firing and reluctant firing (Hu et al, 2016 ). Exemplars of tonic firing at different depolarized membrane potentials were shown in Figure 5C .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Averaged spike frequencies vs. the hyperpolarizing pre-pulses were shown in the right panel ( n = 13 cells in nine rats). Meanwhile, we found that the mean latency to peak of the rebound depolarization was 69.6 ± 19.3 ms at −120 pA. Our previous study has shown that SG neurons exhibit various firing patterns, encompassing tonic firing, delayed firing, single spike, initial burst, phasic firing, gap firing and reluctant firing (Hu et al, 2016 ). Exemplars of tonic firing at different depolarized membrane potentials were shown in Figure 5C .…”
Section: Resultsmentioning
confidence: 64%
“…Spinal cord slices were prepared as our previous studies (Liu et al, 2015 ; Hu et al, 2016 ). Briefly, animals were deeply anesthetized with urethane (1.5 g/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the expression of HCN3 and HCN4 in the CNS appears less abundant. Interestingly, I h currents have also been reported in reactive brain astrocytes as well as pain-processing neurons in the spinal cord [90][91][92]. Interestingly, I h currents have also been reported in reactive brain astrocytes as well as pain-processing neurons in the spinal cord [90][91][92].…”
Section: Decreased Neuronal Activitymentioning
confidence: 97%
“…The reversal potential of I h current (i.e., the x-intercept of the current-voltage curve, which can be represented as V rev ) was also shifted toward hyperpolarized voltages. Such an effect is believed to correspond to the altered ion selectivity of HCN channels (Hu et al, 2016). However, the shift in the V rev of I h current could be also attributed to the effect of leak currents.…”
Section: Discussionmentioning
confidence: 99%